Exploring Indigenous Women’s Dietary Practices with the Women Warriors Program: Social Determinants and Resilience in Seeking Wellness ... - Sampson, Megan Beth (Arts, 2018)
Indigenous women (First Nation, Métis, and Inuit) experience nutrition-related chronic illness at disproportionate rates when compared to both Indigenous men and the Canadian population at large. Negative social determinants of health stemming from recent and historical injustices contribute to this reality. Indigenous women’s position in Canada is distinct as they may face marginalization on the basis of sex, race, and socioeconomic status. Despite these realities, Indigenous feminist literature demonstrates that Indigenous women are often at the forefront of anticolonial movements and attempts to improve wellness within their communities. This research investigates what Indigenous women’s dietary practices reveal about their distinct experiences, needs, preferences, and values relating to food and health. It took place on Treaty 6 territory in the city of Lloydminster and its surrounding rural areas, and includes the experiences of Cree and Métis women. Current public health initiatives targeting ...